MiniApps derived from production HPC applications using multiple programing models. (July 2018) - Messer, OE Bronson; D'Azevedo, Ed; Hill, Judy; Joubert, Wayne; Berrill, Mark; Zimmer, Christopher
We have developed a set of reduced, proxy applications ("MiniApps") based on large-scale application codes supported at the Oak Ridge Leadership Computing Facility (OLCF). The MiniApps are designed to encapsulate the details of the most important (i.e. the most time-consuming and/or unique) facets of the applications that run in production mode on the OLCF. In each case, we have produced or plan to produce individual versions of the MiniApps using different specific programing models (e.g., OpenACC, CUDA, OpenMP). We describe some of our initial observations regarding these different implementations along with estimates of how closely the MiniApps track the actual performance characteristics (in particular, the overall scalability) of the large-scale applications from which they are derived.